The Drosophila microRNA bantam regulates excitability in adult mushroom body output neurons to promote early night sleep - Michael Hobin; Katherine Dorfman; Mohamed Adel; Emmanuel J. Rivera-Rodriguez; Elena A. Kuklin; Dingbang Ma; Leslie C. Griffith (iScience, 2022)
Summary: Sleep circuitry evolved to have both dedicated and context-dependent modulatory elements. Identifying modulatory subcircuits and understanding their molecular machinery is a major challenge for the sleep field. Previously, we identified 25 sleep-regulating microRNAs in Drosophila melanogaster, including the developmentally important microRNA bantam. Here we show that bantam acts in the adult to promote early nighttime sleep through a population of glutamatergic neurons that is intimately involved in applying contextual information to behaviors, the γ5β′2a/β′2mp/β′2mp_bilateral Mushroom Body Output Neurons (MBONs). Calcium imaging revealed that bantam inhibits the activity of these cells during the early night, but not the day. Blocking synaptic transmission in these MBONs rescued the effect of bantam knockdown. This suggests bantam promotes early night sleep via inhibition of the γ5β′2a/β′2mp/β′2mp_bilateral MBONs. RNAseq identifies Kelch and CCHamide-2 receptor as possible mediators, establishing a new role for bantam as an active regulator of sleep and neural activity in the adult fly.